2023
DOI: 10.14218/jcth.2022.00110
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Prolyl Endopeptidase Inhibitor in High-fat Diet-induced Metabolic Dysfunction-associated Fatty Liver Disease

Abstract: Background and Aims:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The latest data suggest that its occurrence is on the rise worldwide, reaching 24% and resulting in a substantial financial burden. 146 A study found that human umbilical cord MSC-EVs containing miR-627-5p could improve insulin tolerance, alleviate liver injury, modulate glucose/lipid metabolism and reduce lipid deposition in an MAFLD rat model. 136 The effects were associated with miR-627-5p targeting and suppressing Fat Mass and Obesity associated (FTO) gene expression.…”
Section: Msc-evs and Metabolism-associated Fatty Liver Disease (Mafld)mentioning
confidence: 99%
“…The latest data suggest that its occurrence is on the rise worldwide, reaching 24% and resulting in a substantial financial burden. 146 A study found that human umbilical cord MSC-EVs containing miR-627-5p could improve insulin tolerance, alleviate liver injury, modulate glucose/lipid metabolism and reduce lipid deposition in an MAFLD rat model. 136 The effects were associated with miR-627-5p targeting and suppressing Fat Mass and Obesity associated (FTO) gene expression.…”
Section: Msc-evs and Metabolism-associated Fatty Liver Disease (Mafld)mentioning
confidence: 99%